Liftings of Nichols algebras of diagonal type I. cartan type A - Andruskiewitsch, Nicolas (2017)
After the classification of the finite-dimensional Nichols algebras of diagonal type[17,18], the determination of its defining relations[7,6], and the verification of the generation in degree-s1 conjecture[6], there is still one step missing in the classification of complex finite-dimensional Hopf algebras with abelian group, without restrictions on the order of the latter: The computation of all deformations or liftings. A technique towards solving this question was developed in[5], built on cocycle deformations. In this paper, we elaborate further and present an explicit algorithm to compute liftings. In our main result we classify all liftings of finite-dimensional Nichols algebras of Cartan type A, over a cosemisimple Hopf algebra H. This extends[2], where it was assumed that the parameter is a root of unity of order >3 and that H is a commmutative group algebra. When the parameter is a root of unity of order 2 or 3, new phenomena appear: The quantum Serre relations can be deformed; this allows in turn the power root vectors to be deformed to elements in lower terms of the coradical filtration, but not necessarily in the group algebra. These phenomena are already present in the calculation of the liftings in type A2 at a parameter of order 2 or 3 over an abelian group[11,19], done by a different method using a computer program. As a byproduct of our calculations, we present new infinite families of finite-dimensional pointed Hopf algebras.